2010
DOI: 10.1186/1743-422x-7-248
|View full text |Cite
|
Sign up to set email alerts
|

Selective gene silencing by viral delivery of short hairpin RNA

Abstract: RNA interference (RNAi) technology has not only become a powerful tool for functional genomics, but also allows rapid drug target discovery and in vitro validation of these targets in cell culture. Furthermore, RNAi represents a promising novel therapeutic option for treating human diseases, in particular cancer. Selective gene silencing by RNAi can be achieved essentially by two nucleic acid based methods: i) cytoplasmic delivery of short double-stranded (ds) interfering RNA oligonucleotides (siRNA), where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 128 publications
(129 reference statements)
1
75
0
3
Order By: Relevance
“…For the expression of a specific transgene in desired cells or tissues with the proper timing, many vectors carrying transgenes have been developed (Mátrai et al, 2010;Nayak & Herzog, 2010;Sliva & Schnierle, 2010). Retroviral, lentiviral, adenoviral, and adeno-associated viral vectors are used in various ways to achieve these goals.…”
Section: Introductionmentioning
confidence: 99%
“…For the expression of a specific transgene in desired cells or tissues with the proper timing, many vectors carrying transgenes have been developed (Mátrai et al, 2010;Nayak & Herzog, 2010;Sliva & Schnierle, 2010). Retroviral, lentiviral, adenoviral, and adeno-associated viral vectors are used in various ways to achieve these goals.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to siRNA, small hairpin RNA (shRNA) is integrated into chromosomal DNA and is constantly expressed to achieve prolonged gene silencing (13). The major advantage of the lentiviral shRNA system is that the shRNA can be delivered into both dividing and nondividing cells to achieve stable long-term effects on target gene silencing; therefore, it can be used for in vivo applications (14). Recently, many studies reported the use of retroviral-and lentiviral-based vector systems for the expression of shRNAs for cancer therapy (15,16).…”
mentioning
confidence: 99%
“…36 However, the use of a viral vector and shRNA is known to induce stable knockdown, whereas siRNAs induce a transient knockdown. 37,38 Our experimental strategy was developed so as to avoid a gene therapy approach, and favor a cell therapy approach to cartilage repair, thereby avoiding the ethical problems behind genome modification. In addition, our study aimed first and foremost at decreasing the expression of type I collagen transiently to initiate the redifferentiation of dedifferentiated chondrocytes.…”
Section: Discussionmentioning
confidence: 99%